Annual Leave Entitlement of Labor (A Comparison between Egypt Law with Indonesia) - Jaedin Jaedin (Walisongo Law Review (Walrev), 2020)
Wages are unimportant in work ties then leave pay is a worker's right that must be provided in accordance with the principle of no work no pay. Leave is a goal to restore labor to a physically stable and able to rest the human body. However, the regulations in Indonesia do not apply the law as in the State of Egypt, the employer revokes the wages of leave if the worker is provided with other services while on leave. Regulations in Egypt are in accordance with the Egyptian Law Number 12 of 2003 concerning relevance to the purpose of the leave itself, namely leave to rest the physical or body of the worker, not to utilize work leave at another employer. However, the regulations in Indonesia in Law Number 13 of 2003 have not been regulated as in Egypt. In Egypt, it is more comprehensive in expressing the principle of no work, no pay.